Effect of mapp as coupling agent on the mechanical properties of palm fiber empty fruit bunch and cellulose polypropylene biocomposites - Khalid, Mohammad; Ali, Salmiaton; Abdullah, Luqman Chuah; Ratnam, Chantara Thevy; Choong, Thomas Shean Yaw (Federation of Engineering Institutions of Islamic Countries, 2006)
In this paper maleic anhydride grafted polypropylene, MAPP (GR-205) was used as a coupling agent for the PP-cellulose (derived from oil palm empty fruit bunch fiber) and PP-oil palm empty fruit bunch fiber (EFBF) biocomposites. Different sets of biocomposites were prepared by blending PP-cellulose and PP-EFBF at a fixed ratio of 70/30 (wt/wt %) using brabender mixer at 180 °C. The MAPP was added at varying concentrations (2, 3, 5, and 7 wt %) during the blending. The biocomposite were subsequently molded with hot press under pressure for the test specimen preparation. The effect of MAPP concentration on the mechanical properties such as tensile, flexural and impact strengths of both the biocomposites were studied. It was found that 30 wt % filler (cellulose and EFBF) loading with 2 wt % MAPP concentration give the best results for the EFBF biocomposites. Nearly 58 % increase in tensile strength of PP-EFBF was observed in respect of control (without MAPP) biocomposite. The MAPP enhanced the EFBF matrix adhesion, resulting in an improvement in EFBF biocomposite performance. On the other hand there were no significant changes observed in the PPcellulose biocomposites properties on addition of MAPP.